Flexural-torsional buckling of cold-formed steel columns with arbitrary cross-section under eccentric axial load. (December 2020) - Ghandi, Elham; Esmaeili Niari, Shirin
Abstract: In recent years, the use of cold-formed steel sections as load bearing components has increased significantly. These sections are susceptible to a variety of cross-section instabilities, including local, distortional, global or a combination of these buckling modes due to their low thickness, so it is necessary to investigate the buckling behavior of these members. In this paper, the flexural–torsional buckling behavior of cold-formed steel columns with arbitrary asymmetric cross section has investigated. For this purpose, using the exact static stiffness matrix method, the differential equations governing column buckling with arbitrary asymmetric cross section have been extracted under eccentrically axial load. Calculating buckling loads using this method results in a nonlinear eigenvalue problem. For solve this problem, Wittrick- Williams algorithm is used. The extracted formulation is predicted to be used to calculate the critical loads of the types of double symmetric, single symmetric and asymmetric cold-formed sections.